2000
DOI: 10.1590/s0004-282x2000000100005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic insomnia in workers poisoned by inorganic mercury: psychological and adaptive aspects

Abstract: ABSTRACR -Insomnia is one of the symptoms of inorganic mercury poisoning (IMP). The objective of this study is to analyze the chief psychological aspects in the adjustment of workers with chronic insomnia associated with IMP. For this purpose the Preventive Clinical Interview and the Ryad Simon Operational Adaptive Diagnostic Scale (Escala Diagnóstica Adaptativa Operacionalizada-EDAO) were utilized. Fifteen subjects with mean age of 40 years (10 males and 5 females) were studied. Nine were diagnosed with High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…Gonzalez-Ramirez et al 30 (1998) 65 A análise da avaliação médica desses trabalhadores será objeto de futura publicação. Constatou-se que os problemas surgiram ora na vigência da exposição, ora muito tempo depois da exposição.…”
Section: Tratamento Com Agentes Quelantesunclassified
“…Gonzalez-Ramirez et al 30 (1998) 65 A análise da avaliação médica desses trabalhadores será objeto de futura publicação. Constatou-se que os problemas surgiram ora na vigência da exposição, ora muito tempo depois da exposição.…”
Section: Tratamento Com Agentes Quelantesunclassified
“…Insomnia and other sleep disorders have been reported subsequent to mercury exposure in worker in fluorescent light bulb plants (Rossini et al, 2000), among sport-fishers in Wisconsin (Knobeloch et al, 2006), among dental assistants exposed to mercury-containing amalgam used in fillings (Moen et al, 2008), among gold miners in Indonesia (Bose-O’Reilly et al, 2016), and among Iranian workers gilding a shrine (Vahabzadeh and Balali-Mood, 2016). Additional research is needed to address the mechanism underlying these sleep disruptions observed with mercury exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Urban workers may become Hg-contaminated through the use of agro-toxic substances containing chlorine-alkalis, the industrial production of Hg-lamps and medical equipment, and the sterilisation of surgical equipments with mercury tensiometres and the handling of dental mixtures containing Hg [5]. Mercury is a potent enzyme inhibitor, with high affinity for -SH groups, highmolecular-weight proteins with membrane structural function [6].…”
Section: Introductionmentioning
confidence: 99%